2015
DOI: 10.1002/stem.2263
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Innate Immune Response by Human Neural Precursors Prevails over Oligodendrocyte Progenitor Remyelination to Rescue a Severe Model of Pelizaeus-Merzbacher Disease

Abstract: Pelizaeus-Merzbacher disease (PMD) results from an X-linked misexpression of proteolipid protein 1 (PLP1). This leukodystrophy causes severe hypomyelination with progressive inflammation, leading to neurological dysfunctions and shortened life expectancy. While no cure exists for PMD, experimental cell-based therapy in the dysmyelinated shiverer model suggested that human oligodendrocyte progenitor cells (hOPCs) or human neural precursor cells (hNPCs) are promising candidates to treat myelinopathies. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 42 publications
(71 reference statements)
4
36
0
2
Order By: Relevance
“…When compared to rodent iPSC‐derived progenies, human iPSC derived progenies generated similarly functional oligodendrocytes (Figure ). Although already committed to the oligodendroglial lineage and the O4+ stage, the transplanted iPSC‐O4+ cells migrated as extensively rostrocaudally and dorsoventrally as hfNPC in the immunodeficient shiverer host, differentiated 3–4 fold more into CC1+ oligodendrocytes and contributed 1.5 fold more to myelination of the dorsal column lesion compared to hfNPC, suggesting as previously demonstrated with fetal cells (Marteyn et al, ), improved (re)myelination when cells are grafted as OPC rather than NPC. Altogether, these data demonstrate that irrespective of their source (fetal or pluripotent), human stem cells/OPCs respond dynamically and interact specifically with the host environment.…”
Section: Comparison Of Rodent and Human Oligodendrocytessupporting
confidence: 72%
See 1 more Smart Citation
“…When compared to rodent iPSC‐derived progenies, human iPSC derived progenies generated similarly functional oligodendrocytes (Figure ). Although already committed to the oligodendroglial lineage and the O4+ stage, the transplanted iPSC‐O4+ cells migrated as extensively rostrocaudally and dorsoventrally as hfNPC in the immunodeficient shiverer host, differentiated 3–4 fold more into CC1+ oligodendrocytes and contributed 1.5 fold more to myelination of the dorsal column lesion compared to hfNPC, suggesting as previously demonstrated with fetal cells (Marteyn et al, ), improved (re)myelination when cells are grafted as OPC rather than NPC. Altogether, these data demonstrate that irrespective of their source (fetal or pluripotent), human stem cells/OPCs respond dynamically and interact specifically with the host environment.…”
Section: Comparison Of Rodent and Human Oligodendrocytessupporting
confidence: 72%
“…These in vitro and in vivo differences between rodent and human cells highlight the necessity to further study the biology of human oligodendroglia to improve our understanding of myelin diseases and the development of therapeutic treatments. Human OPC have been successfully isolated from fetal as well adult brain tissue upon immunoselection for OPC markers such as A2B5 and PDGFRα (Ruffini, Arbour, Blain, Olivier, & Antel, 2004;Sim et al, 2011;Windrem et al, 2002;Windrem et al, 2004), or have been differentiated from fetal brain derived NPC (Marteyn et al, 2016). However, ethical concerns and the scarce access to human brain tissue is a restrictive factor for the isolation and study of primary human OL.…”
Section: Functional Differences Between Human and Rodent Opc Identimentioning
confidence: 99%
“…The remarkable variety of the cellular pathogenesis indicates that no single therapy concept may work for all patients with SPG2 or PMD. Consequently, the therapeutic approaches to SPG2/PMD vary widely, including downregulating the toxic PLP/Plp overexpression (Prukop et al, ), cholesterol‐dependent modulation of intracellular PLP trafficking (Saher et al, ), neuroprotective dietary supplementation with Turmeric (Epplen et al, ; Yu et al, ), stem cell therapy (Gupta et al, ; Marteyn et al, ; Osorio et al, ), manipulating the unfolded protein response (Southwood, Garbern, Jiang, & Gow, ) or microglial proteases and protease inhibitors (Shimizu et al, ), and ablating the activation of T‐lymphocytes (Groh et al, ; Ip et al, ; Ip et al, ). Considering the presence of cytotoxic T‐lymphocytes in the CNS of a wide range of SPG2/PMD models, T‐lymphocytes are probably involved in the progression of axonal pathology in all or most SPG2/PMD spectrum disorders; yet they probably do not explain the axonal pathology to its full extent.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that microglia is associated with the clearance and phagocytosis of degraded and collapsed myelin debris, existence of which is detrimental to OPC proliferation and remyelination (Kotter et al, 2005, 2006; Ruckh et al, 2012; Kocur et al, 2015). Studies also found that microglia, especially M2 phenotype, are positively related to the recruitment of OPCs and their differentiation into mature oligodendrocytes, as well as myelin formation (Miron et al, 2013; Wang et al, 2015; Marteyn et al, 2016). Although EA shows a therapeutic effect on various neurodegenerative diseases achieved by its ability to alleviate existing neuroinflammation and glial dysfunction, it is unclear whether EA could modulate microglia function during the process of demyelination and remyelination.…”
Section: Introductionmentioning
confidence: 99%